Korelasi Program PSN 3M Plus terhadap Perilaku PSN 3M Plus dengan Pendekatan Model Precede-Proceed di Kabupaten Jepara - Lifsi Nurainiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) in Jepara Regency is still an unresolved health problem. The incidence rate reached 960 cases, dominated by the 5-14 year age group and 13 cases of case fatality rate due to dengue fever. The trend in the incidence of dengue fever tends to fluctuate from 2019 to 2023. 3M Plus Mosquito Nest Eradication (PSN) is a program in the effort and control of dengue fever by involving the active role of the entire community. Involves three main steps, namely draining, covering and recycling items that have the potential to become breeding grounds for the Aedes aegypti mosquito as well as additional measures such as using mosquito nets when sleeping and repellent medication. The aim of this research is to determine the correlation between the 3M Plus PSN Program and 3M Plus PSN behavior with the PRECEDE-PROCEED approach in handling dengue hemorrhagic fever cases in Jepara Regency. This type of research is observational analytics using quantitative methods with a cross-sectional design. The population in this study were housewives with an age range of 20-64 years with a research sample of 158. Data were analyzed univariately, bivariately and multivariately using frequency distribution tables and chi square tests. The results of the analysis show that there is no relationship between acceptance of the PSN 3M Plus program with knowledge (p=0.209), practice (p=0.584), support from community leaders (p=0.546), facilities (p=0.742), support from health workers (p=0.849 ), cadre support (p=0.079), and there is a relationship between the PSN 3M Plus program and attitudes (p=0.048).